Brand logos versus brand names: A comparison of the memory effects of textual and pictorial brand elements placed in computer games - Yogesh Dwivedi (Journal of Business Research, 2022)
While a plethora of studies on gamification of advertising exists, little is known about how consumers process different types of brand elements (logos and names) placed in computer games, and whether differences in information processing lead to variations in brand memory. This gap is addressed by conducting three rigorous experiments. In Study 2 we find that, in general, brand logos lead to stronger memory than brand names – something known as the picture superiority effect. Study 3 examines the condition where the picture superiority effect is neutralized. We find that when the speed of a computer game is reduced, names and logos develop similar memory. Finally, in Study 4, we examine whether the picture superiority effect can be neutralized also in the context of high-speed games. We find that in fast games if the physical distinctiveness of the brand elements is increased, both logos and names yield in similar memory.